Sea Surface Temperature Retrievals from Remote Sensing - Jorge Vazquez (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book covers topics ranging from a detailed error analysis of SSTs to new applications employed, for example, in the study of the El Niño-La Niña Southern Oscillation, lake temperatures, and coral bleaching. New techniques for interpolation and algorithm development are presented, including improvements for cloud detection. Analysis of the pixel-to-pixel uncertainties provides insight to applications for high spatial resolutions. New approaches for the estimation and evaluation of SSTs are presented. In addition, an overview of the Climate Change Initiative, with specific applications to SST, is presented. The book provides an excellent overview of the current technology, while also highlighting new technologies and their applications to new missions.